Business capital accumulation and the user cost: is there a heterogeneity bias? - Serena Fatica (Publications Office of the European Union, 2017)
Empirical models of capital accumulation estimated on aggregate data series are based on the assumption that capital asset types respond in the same way to cost variables. Likewise, aggregate models do not consider potential heterogeneity in investment behaviour originating on the demand side for capital, e.g. at the sector level. We show that the underlying assumption of homogeneity may indeed lead to misspecification of standard aggregate investment models. Using data from 23 sectors in 10 OECD countries over the period 1984-2007, we adopt a fully disaggregated approach – by asset types and sectors – to estimate the responsiveness of investment to the tax-adjusted user cost of capital. While accounting for the different sources of heterogeneity, we find that fixed capital accumulation is significantly affected by changes in the user cost. However, the estimated substitution elasticities are smaller than one - the benchmark value under a Cobb-Douglas production function. We do not find robust evidence that the long run substitution elasticities are statistically different across asset types.
Keywords: E22; H25; C33; 330; capital accumulation; user cost of capital; corporate taxation; panel data